Tourism Village Community Empowerment Strategy in Supporting the Local Potential of the Village in Magetan Regency (Study Village Tour Genilangit, Poncol, Magetan, East Java) - Priska Septiana Margareta; Saiman Saiman; Iradhad Taqwa Sihidi (Budapest International Research and Critics University, 2022)
This study aims to analyze the tourism village community empowerment strategy in supporting the local village potential in Genilangit Village, Magetan Regency. This research method uses qualitative and case studies. Data was collected through interviews, observations, and documented data. Informants consist of primary informants and secondary informants. The results of the study indicate that the strategy of empowering the tourism village community in Genilangit Village, Magetan Regency is carried out in three stages, namely first, public awareness of the village's potential which is carried out by door to door socialization. Second, community capacity building is carried out by training both physically and mentally through training or socialization to improve human resources. Third, the provision of power in the form of providing power, authority or opportunities for rural communities to develop and achieve independence. One of these resources is the provision of assistance in the form of plant seeds or trees to the community for development. The impact of community empowerment in the tourist village area is very impactful for the village community. One of them is the declining unemployment rate due to the creation of new jobs, besides that it also adds new income for the community and the migration rate is low because people have the opportunity to develop in their own villages without having to leave the region or abroad.